Optimizing the Use of Recycled Drinking Water Treatment Sludge in Paving Block Production - Eka Putra, Reza; Ismayana, Andes; Putra, Heriansyah (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Drinking Water Treatment Sludge (DWTS) recycling is a solution for handling waste sludge by making paving blocks. This paper analysis the optimization of the mechanical performance, durability, and cost production of the paving block incorporating recycled DWTS as a replacement for fine aggregate. Three paving block mixes were produced, and the replacement of sand aggregates by DWTS aggregate was mixed into different percentages by weight with variations in the water-tocementitious ratio (w/c). The mechanical performance and durability significantly decreased, falling well below the quality criteria, with the addition of DWTS increasing by over 40%. The obtained result indicated that DWTS could be used as an adequate replacement for sand aggregate that met the optimum level in the paving block containing 40% sludge with w/c 0.8 could achieve a 28-day compressive strength of 11.64 MPa, a density of 1,866.27 kg/m³, a water absorption of 12.61%, and a wear resistance of 0.077 mm/minute. It was the optimal replacement value that met the quality requirements for Class D (park). It has utilization of DWTS in paving block could help develop the appropriate technology and increase production cost efficiency to 7.73% equivalent 72,697.82 IDR/m3 paving block, thus significantly resulted in product meets technical reliability and low-cost.